Unconditional cash transfers and mental health symptoms among parents with low incomes: Evidence from the 2021 child tax credit - Nicole Kovski; Natasha V. Pilkauskas; Katherine Michelmore; H. Luke Shaefer (Elsevier, 2023)
The COVID-19 pandemic increased anxiety and depression in the U.S. population, particularly among low-income households, parents, and Black and Hispanic adults. To address the negative impacts of the pandemic, Congress temporarily expanded the Child Tax Credit (CTC) in 2021, providing a near-universal, unconditional cash transfer to families with children. Using a quasi-experimental, parameterized difference-in-differences research design, we examine the effects of the 2021 monthly CTC on symptoms of anxiety and depression in a large, national sample of parents with low incomes (N∼15,000). We study potential differences in the associations by race/ethnicity and consider whether CTC effects were stronger after a longer treatment period (for instance, due to greater dosage or delayed effects). We find some evidence that the monthly credit reduced parental anxiety and depression symptoms, although the results were not robust throughout all model specifications. Analyses stratified by race/ethnicity show stronger associations for non-Hispanic Black parents than for non-Hispanic White parents or Hispanic parents, although differences were small. We also find the credit reduced anxiety (but not depression) symptoms after three months of payments, suggesting that it took some time for the CTC to affect mental health symptoms. Overall, this study suggests that recurring cash transfers to families in poverty in the U.S. may have small beneficial effects on parental mental health.